THE USE OF POP-UP DICTIONARY FOR ENGLISH VOCABULARY LEARNING FOR PRIMARY SCHOOL LEVEL - Prasarntong, Nutthida; Dennis, Nutprapha (International Journal of Research -GRANTHAALAYAH, 2016)
The purpose of this study was to study students’ opinions toward using Pop-up Dictionary to enhance English vocabulary learning. The instruments of the study were 1) Pop-Up Dictionary 2) questionnaire. The researcher chose all students in Pratomsuksa 5 to be population. The methodologies of this study were 1) Set the objectives and goals of the study. 2) Study English curriculum and choose the contents for creating the material. 3) Design research methodology. 4) Construct the research instruments, the lesson plans, an observation form, and the questionnaire. Then, let the experts check the research instruments. 5) Students study by using Pop-up, teacher observes the students’ behavior and lets the students take the questionnaire, respectively. 6) Evaluate and analyze the students’ scores from the questionnaire. The research findings indicated that: The students’ opinion about vocabulary learning by using Pop up Dictionary pointed that the students’ behaviors were sometimes motivated to be better”. Moreover, many students suggested that they want to learn by using Pop-Up Dictionary. It shows that many students had positive attitude to learn vocabulary by using Pop-Up Dictionary.